2010
DOI: 10.1128/jcm.01780-09
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry for Direct Bacterial Identification from Positive Blood Culture Pellets

Abstract: An ammonium chloride erythrocyte-lysing procedure was used to prepare a bacterial pellet from positive blood cultures for direct matrix-assisted laser desorption-ionization time of flight (MALDI-TOF) mass spectrometry analysis. Identification was obtained for 78.7% of the pellets tested. Moreover, 99% of the MALDI-TOF identifications were congruent at the species level when considering valid scores. This fast and accurate method is promising.Blood cultures are the best approach to establishing the etiology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
137
4
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(158 citation statements)
references
References 6 publications
14
137
4
3
Order By: Relevance
“…Several studies have shown that MALDI-TOF MS analysis of samples obtained directly from positive blood cultures can correctly identify 66% to 97% of aerobic and anaerobic organisms causing monomicrobial bacteremia (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). As in the current study, the best results have been obtained with Gram-negative organisms.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Several studies have shown that MALDI-TOF MS analysis of samples obtained directly from positive blood cultures can correctly identify 66% to 97% of aerobic and anaerobic organisms causing monomicrobial bacteremia (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). As in the current study, the best results have been obtained with Gram-negative organisms.…”
supporting
confidence: 73%
“…Implementation of MALDI-TOF MS in the microbiology laboratory in conjunction with antibiotic stewardship has been associated with earlier initiation of effective antimicrobial therapy and lower 30-day mortality in patients with bloodstream infections (3). This technology has also been applied to reduce turnaround times for identification of blood culture isolates directly from positive blood culture broths (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Various techniques have been assessed, generally involving lysis/centrifugation of blood culture pellets in preparation for analysis by MALDI-TOF MS.…”
mentioning
confidence: 99%
“…One such system, the MALDI Biotyper system (Bruker Daltonics Inc., Billerica, MA), has been successfully used to rapidly identify yeast-like fungal pathogens after they grow on solid medium as pure colonies (2,5,17,28,32). Although direct identification from blood culture media has been successfully applied to bacterial pathogens (8,9,15,22,27), published studies are limited and have yielded variable results for direct identification of yeast-like fungal pathogens directly from positive blood culture medium (8,9,16).…”
mentioning
confidence: 99%
“…With a special set of MALDI Sepsityper is possible to identify bacteria directly from the positive blood culture (17)(18)(19)(20)(21)(22)(23)(24)(25). Most reports describe the blood culture must be grown in automated BACTEC system vials (26,27).…”
Section: An Evaluation Of Direct Identification Of Pathogens From Blomentioning
confidence: 99%